Training Needs Analysis: Study on Development of School Administration's Competence - Ahmad Sabandi; Anisah Anisah; Rusdinal Rusdinal (Journal of Educational Review and Research, 2018)
The objectives of this research are (1) to identify the competency level of school administration staff (SAS), and (2) to analyze the need of SAS Training. This research was conducted using descriptive method. The population of this research is Junior High School Vocational School Administration of West Sumatera which is spread over 18 districts / cities. The sample of the research was taken by geographic cluster and selected 7 (seven) regions. In detail the sample consisted of 158 school administrative staff and 63 heads of administrative staff. The research instrument is a questionnaire with semantic scale that has been tested validity and reliability empirically and obtained significant results. Data analysis was done descriptively. The results showed that the average of head managerial competence of SAS was 78.86% (in the category capable), technical competence of SAS head of 79.14 (in the category capable), technical competence of SAS of 82.75 (in the able category); Meanwhile, the need for education and training in the development of managerial competence of head of SAS is 83.09 (in need category), technical competence of head of SAS is 82.86 (in need category), and technical competence of SAS is 82.30 (in need category).